THE COMPARISON OF STUDENT’S ABILITY BETWEEN GRADUATE OF SENIOR HIGH SCHOOL (SMU) AND ISLAMIC SENIOR HIGH SCHOOL (MA) IN USING PREPOSITION INTO SENTENCE AT FIRST GRADE AND SECOND GRADE OF KELUARGA BUNDA JAMBI MIDWIFERY ACADEMY - Rahmah, Rahmah (LPPM Universitasdiwangsa Jambi, 2019)
Traditional English grammar classifies the words into eight parts of speech, such has noun, verb , adverb, adjective, conjunction, pronoun, preposition, and interjection (Yule:2004). When someone tries to describe about preposition of place and time, they must give information clearly about anyone their mean to say. in this research, researcher interests to appoint this problem by comparison of student?s ability between graduate of Senior High School (SMU) and Islamic Senior High School (MA) in using preposition into sentence. The method had used in this research was descriptive quantitative. The population in this research are all of students of first grade and second grade of Keluarga Bunda Jambi Midwifery Academy. The sample in this research was 45 students first grade and second grade of Keluarga Bunda Jambi Midwifery Academy consists of 18 students from SMU and 27 students from MA. The result of this research show that score of the students graduate from SMU is 88 highest and 56 lowest, score of the students graduate from MA is 84 highest and 52 lowest. Based on interpretation result with having calculated to table ?t? score with df N1+N2-2=43, because there is no df 43, so take df 45. Then this value consult with table of ?t? in the significant rating 5% and 1%. The result of analysis data is 0,11 if calculated to the score of critical (t table) so, 2,02>0,11<2,69, it is mean that Ha is refused and Ho is received and it is mean that there is no significant differences between the ability of the students from graduated fo SMUand MA in using preposition into sentences.